KEPUASAN PELANGGAN YNAG MENGINAP DI HOTEL GRAND CENTRAL PEKANBARU - Puspa Anggraini; Firdaus Yusrizal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research aims to determine customer satisfaction at hotel Grand Central Pekanbaru to the service quality which consists of five dimensions which are tangible, reliability, responsiveness, assurance, and empathy.This study uses Importance Performance Analysis (IPA) or level of interest analysis and performance or customer satisfaction. The population of this study are all customers who have ever come or have used services at the Grand Hotel Pekanbaru. The sample of this research is 100 respondents from hotel guest by the accidental sampling method. Based on the research that has been done, the data processing indicates that respondents to the Grand Central Hotel Pekanbaru obtain excellent results. Where all the average values indicate the level of conformity the reality and expectations of respondents exceeded from 1 or greater than 100%, which is stated with great satisfaction.Keyword: Customer Satisfaction, Service Quality, Tangible, Reliability, Responsiveness, Assurance, Empathy